Frequency‐Dependent Habituation Deficit of the Nociceptive Blink Reflex in Aura With Migraine Headache. Can Migraine Aura Modulate Trigeminal Excitability?. Issue 6 (10th May 2017) - Perrotta, Armando; Anastasio, Maria Grazia; De Icco, Roberto; Coppola, Gianluca; Ambrosini, Anna; Serrao, Mariano; Sandrini, Giorgio; Pierelli, Francesco
Abstract : Objective: To study the influence of the migraine aura on the trigeminal nociception, we investigated the habituation of the nociceptive blink reflex (nBR) R2 responses in aura with migraine headache (AwMH) and comparatively in migraine without aura (MWoA) and healthy subjects (HS). Background: A clear deficit of habituation in trigeminal nociceptive responses has been documented in MWoA; however, similar data in MWA are lacking. Methods: Seventeen AwMH, 29 MWoA, and 30 HS were enrolled and a nonrandomized clinical neurophysiological study examining nBR habituation by clinical diagnosis was devised. We delivered a series of 26 electrical stimuli, at different stimulation frequencies (SF) (0.05, 0.1, 0.2, 0.3, 0.5, and 1 Hz), subsequently subdivided in five blocks of five responses for each SF. The mean area values of the second to the fifth block expressed as the percentage of the mean area value of the first block were taken as an index of habituation for each SF. Results: A significant lower mean percentage decrease of the R2 area across all blocks was found at 1, 0.5, 0.3, and 0.2 Hz SF in MWoA and at 0.3 and 0.2 Hz SF in AwMH, when compared to HS. In the most representative fifth block of responses, we found in MWoA vs HS at 1 Hz, 57.0 ± 27.8 vs 30.6 ± 12.0; at 0.5 Hz, 54.8 ± 26.1 vs 32.51 ± 17.7; at 0.3 Hz, 44.7 ± 21.6 vs 27.6 ± 13.2; at 0.2 Hz, 61.3 ± 29.5 vs 32.6 ± 18.0, and in AwMH vs HS at 0.3 Hz, 52.7 ± 24.7 vs 27.6 ± 13.2; at 0.2 Hz, 69.3 ± 38.6 vs 32.6 ± 18.0 as mean ± SD of the R2 area percentage of the first block, respectively. Interestingly, AwMH subjects did not show differences in mean percentage decrease of the R2 area at 1 and 0.5 Hz SF when compared to HS. No differences between groups were found at 0.1 and 0.05 Hz SF. Conclusions: We demonstrated in AwMH a deficit of habituation of the nBR R2 responses after repeated stimulations, although less pronounced than that observed in MWoA of comparable clinical severity. We hypothesize that AwMH and MWoA share some pathogenetic aspects, and also that migraine aura physiopathology may play a modulating role on the excitability of the nociceptive trigeminal pathways.